Annexin A2-Mediated Plasminogen Activation in Endothelial Cells Contributes to the Proangiogenic Effect of Adenosine A2A Receptors - Valls, María D.; Soldado, María; Arasa, Jorge; Perez-Aso, Miguel; Williams, Adrienne J.; Cronstein, Bruce N.; Noguera, M. Antonia; Terencio, M. Carmen; Montesinos, M. Carmen (Frontiers in Pharmacology, 2021)
Adenosine A2A receptor mediates the promotion of wound healing and revascularization of injured tissue, in healthy and animals with impaired wound healing, through a mechanism depending upon tissue plasminogen activator (tPA), a component of the fibrinolytic system. In order to evaluate the contribution of plasmin generation in the proangiogenic effect of Adenosine A2A activation, we determined the expression and secretion of t-PA, u-PA, PAI-1 and annexin A2 by human dermal microvascular endothelial cells (HDMVEC) stimulated by the selective agonist CGS-21680. The plasmin generation was assayed through an enzymatic assay and the proangiogenic effect was studied using an endothelial tube formation assay in Matrigel. Adenosine A2A receptor activation in endothelial cells diminished the release of the plasminogen activator inhibitor-1 (PAI-1) and promoted the production of annexin A2, which acts as a cell membrane co-receptor for plasminogen and its activator tPA. Annexin A2 mediated the increased cell membrane-associated plasmin generation in adenosine A2A receptor agonist treated HDMVEC and is required for tube formation in an in vitro model of angiogenesis. These results suggest a novel mechanism by which adenosine A2A receptor activation promotes angiogenesis; increased endothelial expression of annexin A2, which, in turn, promotes fibrinolysis by binding tPA and plasminogen to the cell surface.